Patterns of physical activity amidst COVID-19 among medical interns - Debata, Ipsita; Mohapatra, Ipsa; Sarkar, Avinandan; Sarkar, Bidisa; Sahu, Ritu; Padhee, Sourav (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The COVID-19 pandemic restricted our daily lives significantly. This adversely affected the physical activity (PA) and productivity of students, including medical interns, who worked tirelessly during the pandemic. The study aimed to evaluate the changes in PA patterns and associated factors due to the imposed lockdown in medical interns compared to pre-pandemic levels. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A cross-sectional study was conducted among consenting medical interns of the 2020-21 batch in a medical college in Bhubaneswar, selected by convenience sampling. They were contacted by email and briefed about the study. Data on demography, exercise patterns (pre-, during, and post-COVID-19), and associated factors was collected by an electronic survey format (Google form). Data was analyzed using EPI info and interpreted in frequencies, percentages, and the chi-square test. A p-value<0.05 was considered statistically significant. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Of 104, 54.28% were females. The frequency of exercise reduced by 13.92% during COVID-19. Around 56.9% of interns exercised regularly pre-pandemic which dropped to 33.3% during the pandemic. The change in PA pattern was significantly associated with regularity of exercise (p<0.001). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Evaluating the extent of physical inactivity will enable the administration to provide appropriate support to the interns to take equal care of their health as their patients.